Effects of Information Provision on Undocumented Migration to Europe: Evidence from a Survey Experiment - Jean-Michel Lafleur; Abdeslam Marfouk (Global Labor Organization (GLO), 2025)
Using an experimental design embedded within a nationally representative survey implemented in Algeria, this study seeks to evaluate the effect that information campaigns have on willingness of individuals residing in the Global South to engage in unauthorized migration to Europe. In particular, in line with the discursive priorities of policy-makers focused on deterrence of irregular migration, we examine the impact of messages on the "risks and dangers associated with illegal migration", "anti-migrants walls and other fences", "undocumented immigrants regularization programs" and "access to welfare". Using an experiment embedded within a national survey implemented in Algeria, we did not find any statistically significant effect of information provision on those issues on the willingness of individuals to engage in irregular migration to Europe. These results question the efficiency and legitimacy of the existing approach to migration-information campaign. They also dispute the frequently used argument in policy debates that regularization programs and immigrants' access to welfare trigger undocumented migration.
Keywords: C99; F22; J61; J68; 330; International Migration; Migration-Information Campaigns; Survey Experiments; Undocumented Migration